Os instrumentos da pesquisa científica Rumo a uma plataforma teórica que esclarece e gratifica - de la Lama Zubirán, Paula (2022)
This article describes the state-of-the-art of science instruments and assesses their usefulness, their potentialities and also their limitations. It proposes criteria to select them and thus carry out the research. It addresses the theoretical discussions around qualitative and quantitative instruments; and proposes another way of classifying them, showing that they can reach the replicability requirements, in certain circumstances. Since documentary and experimental fieldwork is one of the fundamental facets of research, it is suggested to do it with a playful spirit to achieve a degree of satisfaction that is only observed in creative activities.